Implementasi Blueprint Sistem Informasi Monitoring Pelanggaran Siswa di MAN 1 Padangsidimpuan dalam Bentuk Aplikasi Website - Rizqi Nusabbih Hidayatullah Gaja; Billy Hendrik (Lembaga Pengembangan Kinerja Dosen, 2023)
This research intends to incorporate a blueprint design for a student violation information system that was developed in earlier research into a website-based application to record student violations at MAN 1 Padangsidimpuan. The needs analysis, system design, software development, testing, and implementation phases of the website application development process are all included in this study's waterfall methodology. The PHP programming language, the CodeIgniter framework, and the MySQL database were used to create this application. This study produced a web tool that MAN 1 Padangsidimpuan can utilize to more efficiently monitor student infractions. This program is anticipated to assist schools in managing student infractions, delivering transparency to both students and parents, and enhancing student conduct in the classroom.